DOI: 10.31274/rtd-180813-12618
|View full text |Cite
|
Sign up to set email alerts
|

The development and evaluation of an experiential computer simulation for animal science students

Abstract: This reproduction was made from a copy of a manuscript sent to us for publication and microfilming. While the most advanced technology has been used to pho tograph and reproduce this manuscript, the quality of the reproduction is heavily dependent upon the quality of the material submitted. Pages in any manuscript may have indistinct print. In all cases the best available copy has been filmed. The following explanation of techniques is provided to help clarify notations which may appear on this reproduction. 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…The results of the study concluded that, although the model as developed provided the structure and documentation to plan full implementation, it was not feasible for an individual to maintain and support the model and that it was difficult to transfer the model and its programming language from one piece of computer hardware to another. Coyle (1985) noted a gap between state-of-art educational research and what is practiced today. The majority of available Computer Assisted Learning (CAL) software at the time, however, lacked appropriate design features that would enable the computer to meet its potential for an infusion of problem solving, information processing, and model building skills into the current curriculum.…”
Section: Studies Reporting Positive Esects Of Computer Simulationmentioning
confidence: 99%
See 1 more Smart Citation
“…The results of the study concluded that, although the model as developed provided the structure and documentation to plan full implementation, it was not feasible for an individual to maintain and support the model and that it was difficult to transfer the model and its programming language from one piece of computer hardware to another. Coyle (1985) noted a gap between state-of-art educational research and what is practiced today. The majority of available Computer Assisted Learning (CAL) software at the time, however, lacked appropriate design features that would enable the computer to meet its potential for an infusion of problem solving, information processing, and model building skills into the current curriculum.…”
Section: Studies Reporting Positive Esects Of Computer Simulationmentioning
confidence: 99%
“…The findings of this study, contrast with the results of some other studies. Eucker (1984), Dick (1985), Coyle (1985), and Thomas and Hooper (1991), indicated that using computer simulation would enhance the learning process.…”
Section: Recommendationsmentioning
confidence: 99%